Coach wooden's leadership game plan for success : 12 lessons for extraordinary performance and personal excellence - Wooden, John, 1910-2010 (McGraw-Hill, 2009)
"Coach Wooden's Leadership Game Plan for Success presents a unique opportunity to study under the man ESPN hails as 'the greatest coach of the 20th century.' Practicing character-based leadership before the term was invented, John Wooden consistently led his legendary teams to victory and has since taught countless business leaders his fundamentals for achieving and sustaining success. This unique tutorial introduces you to his core fundamentals of success as a leader and reinforces them with examples, exercises, quizzes, and quotations."--Resource description page.